Coffee berry husk extract, thyme essential oil and acibenzolar-S‑methyl in the control of brown eye spot of coffee tree - Pereira, Ricardo Borges; Alves, Eduardo; Júnior, Pedro Martins Ribeiro; Resende, Mário Lúcio Vilela de; Lucas, Gilvaine Ciavareli; Ferreira, Josimar Batista (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to assess the effect of the coffee berry husk extract, thyme essential oil and acibenzolar-S-methyl on the germination and micelial growth and on in vivo development of Cercospora coffeicola, and to characterize their effi ciency as resistance inducers in coffee plants, and to determine the peroxidase activity and lignin accumulation in tissues of coffee tree. The coffee berry husk extract presented no toxic effect on germination; however, it inhibited the mycelial growth proportionally to the increase of the concentrations. The thyme essential oil inhibited the germination and the mycelial growth with the increase of concentrations. Both coffee berry husk extract and acibenzolar-S-methyl neither affected the germination nor the development of germinative tubes, differently of thyme essential oil. Seedlings treated with acibenzolar- S-methyl, coffee berry husk extract and thyme essential oil presented peaks of peroxidase activity at 2nd and 11th, 7th and 11th and, 2nd and 9th days after treatment, respectively. The treatments did not differ in lignin content. Coffee berry husk extract and acibenzolar-S-methyl induced resistance in coffee seedlings against C. coffeicola, and thyme essential oil presented toxic effect on the pathogen.